2022
DOI: 10.3389/fgene.2022.859513
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasma Extrachromosomal Circular DNA in Gouty Arthritis

Abstract: Objective: Extrachromosomal circular DNA elements (eccDNAs) are known for their broad existence in cells and plasma, which may potentially play important roles in many biological processes. Our aim was to identify potentially functional or marked eccDNAs in gout patients.Methods: The Circle-Seq approach was applied for eccDNA detection from plasma in acute gout patients and healthy controls. Further analysis was performed on the distribution of genomic elements and eccDNA gene annotations in two groups.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
4
12
0
Order By: Relevance
“…To investigate the mechanism of eccDNA origin, the sequence pattern near the breakpoint has attracted significant research attention. 34,35 Therefore, we examined the DNA sequences flanking the start and end sites of eccDNAs within a 10 bp region to compare the nucleotide composition resulting from different protocols (Fig. 6a and S3†).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the mechanism of eccDNA origin, the sequence pattern near the breakpoint has attracted significant research attention. 34,35 Therefore, we examined the DNA sequences flanking the start and end sites of eccDNAs within a 10 bp region to compare the nucleotide composition resulting from different protocols (Fig. 6a and S3†).…”
Section: Resultsmentioning
confidence: 99%
“…As its distinct topological structure and enigmatic functions in cells, eccDNA, the "magic" mobile and circular DNA molecule, has attracted increasing research interest in recent years. Although numerous studies suggested its potential role in various physiological and pathological statuses, including tumorigenesis [7,21,26], drug-resistance [16,34], aging [35,36], human reproduction [4,8,9] and immune-response [24,37,38], the detailed molecular role of eccDNA remains to be elucidated. One major hurdle in the area is the lack of a rapid and cost-effective method for eccDNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, by comparing sequences between the transcripts of the TTN gene and the associated eccDNA sequences, they proved that its production resulted from TTN circle and demonstrated that a fraction of eccDNAs residing inside the nucleus had transcription functions ( Møller et al, 2018 ). A new study characterized plasma eccDNA in gouty arthritis and identified several eccDNA genes such as COL1A1 and EPB42, which were considered to be closely associated with hyperuricemia and gout ( Pang et al, 2022 ). Several genes involved in inflammation or immune response were also identified by enrichment analysis.…”
Section: Eccdna In Human Diseasesmentioning
confidence: 99%